Quality of life in pediatric oncological disease: Integrative literature review - Santos, Bárbara (2022)
Abstract in proceedings of the Fourth International Congress of CiiEM: Health, Well-Being and Ageing in the 21st Century, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from 3–5 June 2019.